The Influence of TikTok Content Creator on Consumptive Behavior of Teenagers in Online Shopping - T. Titi Widaningsih; Marcellio M.W. Kusumaningrat; Rustono Farady Marta (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
The research will review the effect of Content Creator on adolescent consumptive behavior. The object of research is the TikTok account @carlendoraa. The research population is the followers of the TikTok account @carlendoraa, most of which are teenagers, amounting to 374,000. Determination of the sample uses the Slovin formula, which obtained a total sample of 100 people. The correlational research method is used to determine research hypotheses and the data will be analyzed using Pearson Product Moment Correlation. The results of the research display a significant value of 0.018 < 0.005, which means that there is a correlation between the content creator of Tiktok @carlendoraa and the consumer behavior of teenagers in online shopping. The correlation value of 0.237 implicates a relatively weak, albeit significant correlation between content creator Tiktok @carlendoraa and adolescent consumptive behavior in online shopping.